Pengaruh Komitmen Organisasional Dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai Kantor Bupati Kabupaten Solok Selatan - Zikri Insan; Zusmawati Zusmawati (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The purpose of this study was to examine the effect of organizational and environmental commitment variables on job satisfaction of employees of the South Solok Regency Regent Office. This type of study uses quantitative methods, data collection through the distribution of questionnaires to 80 saturated sampling techniques, namely sampling techniques if all members of the population are used as samples. Hereby using instrument test testing, (validity test and reliability test), classical assumption test (normality test, multicolonarity test and heterokedasticity test), then multiple linear regression and hypothesis test with the help of SPSS application. The results of the study show that organizational commitment has a positive and significant effect on job satisfaction of employees of the South Solok Regency Regent Office and the work environment has a positive and significant influence on the job satisfaction of South Solok Regent Office employees.